Helicobacter Pylori HP(2–20) Induces Eosinophil Activation and Accumulation in Superficial Gastric Mucosa and Stimulates VEGF-α and TGF-β Release by Interacting with Formyl-Peptide Receptors. (July 2013) - Prevete, N.; Rossi, F.W.; Rivellese, F.; Lamacchia, D.; Pelosi, C.; Lobasso, A.; Necchi, V.; Solcia, E.; Fiocca, R.; Ceppa, P.; Staibano, S.; Mascolo, M.; et al.
Eosinophils participate in the immune response against Helicobacter pylori, but little is known about their role in the gastritis associated to the infection. We recently demonstrated that the Hp(2–20) peptide derived from H. pylori accelerates wound healing of gastric mucosa by interacting with N-formyl peptide receptors (FPRs) expressed on gastric epithelial cells. The aim of the present study was to investigate whether eosinophils play a role in the repair of gastric mucosa tissue during H. pylori infection. Immunohistochemistry and transmission electron microscopy were used to detect eosinophils in gastric mucosal biopsies. Eosinophil re-distribution occurred in the gastric mucosa of H. pylori -infected patients: their density did not change in the deep mucosal layer, whereas it increased in the superficial lamina propria just below the foveolar epithelium; eosinophils entered the epithelium itself as well as the lumen of foveolae located close to the area harboring bacteria, which in turn were also engulfed by eosinophils. The H. pylori -derived peptide Hp(2–20) stimulated eosinophil migration through the engagement of FPR2 and FPR3, and also induced production of VEGF-A and TGF-β, two key mediators of tissue remodeling. We also demonstrate that Hp(2–20) in vivo induced eosinophil infiltration in rat gastric mucosa after injury brought about by indomethacin. This study suggests that eosinophil infiltrate could modulate the capacity of gastric mucosa to maintain or recover its integrity thereby shedding light on the role of eosinophils in H. pylori infection.